(untitled) (GIST – Education and Learning Research Journal, 2019)
The role of cultural identity in bilingual programs has been barely discussed in regards to SLA. This research focuses on providing relevant information that helps in having more knowledge about the experiences that an elementary student has during the second language learning process in a bilingual program within a multicultural context. This qualitative study took place in a Dual Language Program in a public elementary school, in Northern Virginia, USA, where 17 students were immersed in a 50:50 program, that is, 50% of classes were in English and the other 50% in Spanish The information was collected by using in person interviews, focus group sessions, and participants and field observations. Receiving others’ influence; living situations as determiners of languages switch, and using two languages as a key aspect in self-esteem improvement, were the experiences which emerged as the ones which contributed in children’s cultural identity formation.